Photocatalytic degradation of reactive black 5 by fish scale-loaded TiO 2 composites - Ho, Li Ngee; Ong, Soon-An; Yee, Lin See (Springer Science+Business Media B.V., 2013)
Link to publisher's homepage at http://link.springer.com/